A power quality comprehensive treatment device for distribution network - XIANG ZENG; ZHU ZHIWEI; WANG LEPENG; XU HUIMING; HU XIAOJUN; LI JIANLIN; FAN QIANGJUN; WEI YANQING; CAO CHANGLONG; CHEN JUNLING; SHAO HAI; YAO PENG (2017)
The utility model belongs to the technical field of electric power system's power quality management, especially, relate to a power quality comprehensive treatment device, the problem of the technique is solved for: the utility model provides a collect this several kinds of functions in a power quality comprehensive treatment device for distribution network of an organic whole of reactive compensation, harmonic compensation, unbalance compensation and low voltage compensation, the technical scheme who adopts does: a power quality comprehensive treatment device for distribution network, concatenates between power U1 and load FZ1, the power quality comprehensive treatment device includes: main circuit and control circuit, the main circuit includes: transformer TR, filter component LC, filter reactor la, the one or three inverter CON1 and the two or three inverter CON2, the utility model is suitable for an electric power system. 本实用新型属于电力系统的电能质量管理的技术领域，尤其涉及种电能质量综合治理装置；解决的技术问题为：提供种集无功补偿、谐波补偿、不平衡补偿以及低电压补偿这几种功能于体的用